Ṭarīqat Taʿlīm Qirāʾat al-Ḥurūf al-Hijāʾiyyah al-ʿArabiyyah li-Mutakhallifī al-ʿAql - Ahmad Faruq Abdullah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
Reading is one of the four fundamental language skills and represents a cognitive process that involves the use of the human mind. The process of reading begins with several stages that ultimately lead to the recognition of alphabetic letters, enabling learners to identify individual letters and connect them to form meaningful words. An important question arises: How can Arabic alphabet reading be effectively taught to learners with intellectual disabilities? Does this group of learners require a specialized instructional method? This article addresses these questions by discussing appropriate methods for teaching the reading of Arabic letters to students with intellectual disabilities. The topic is of considerable importance because reading constitutes the foundation of knowledge acquisition and serves as the primary gateway to learning. Therefore, identifying effective instructional approaches for these learners is essential to support their language development and educational progress.